A study on the factors of barriers to female university students' sports participation from an environmental perspective - Rongjing Ni; Ying Yu (Universitas Negeri Malang, 2023)
Objective: To understand the barriers to sports participation of Chinese female university students and to increase their motivation to participate in sports. Methods: A survey of 1892 female undergraduates aged 18 to 22 who were enrolled in the university was conducted mainly by questionnaire method, and t-test and reliability analysis were conducted using SPSS, and validated factor analysis was conducted using Amos software. Results: Venue environment, natural environment and sports atmosphere are common strong perception factors, while interpersonal environment, social sports environment and policy environment are common weak perception factors. All indicators in the dimension of site environment and natural environment are common strong perception factors. The interpersonal environment dimension, in which people around us do not like sports, the sports environment, in which participation in the environment lacks a sense of belonging, and the policy environment, in which there are fewer sports activities for women in the neighborhood and the lack of sports facilities for women in the surrounding sports venues, are all common strong perception factors for both groups of female college students. Conclusion: Sports participation of female college students from an environmental perspective is influenced by multiple factors, and a complete support system should be built from various aspects such as family, school, and community.